2020
DOI: 10.1186/s12889-020-09839-3
|View full text |Cite
|
Sign up to set email alerts
|

Serious non-fatal unintentional injuries among in-school adolescents in Sri Lanka: results from the 2016 Sri Lankan global school-based health survey

Abstract: Background Unintentional injuries among adolescents is a major public health problem the world over. A great majority of the annual deaths among adolescents is due to unintentional injuries; it is also the leading cause of death among adolescents in the world. The aim of this study was to estimate the incidence of injuries and their associated factors among school going adolescents aged 13–17 years using data from the most recent Global School-Based Health Survey (GSHS) conducted in Sri Lanka. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 21 publications
0
6
1
Order By: Relevance
“…A study done in Saudi Arabia showed that within the last 12 months, the prevalence of unintentional injuries in children was 24.7%, which was lower than other studies that reported a range of 35.8%-42.9% unintentional injuries among adolescents within the same time period, especially among the 13-15 age group [8][9][10][11][12]. Moreover, this study, being consistent with others, states that boys have a higher risk of injury and mortality [8][9][10][11]13,14].…”
Section: Introductionmentioning
confidence: 74%
See 1 more Smart Citation
“…A study done in Saudi Arabia showed that within the last 12 months, the prevalence of unintentional injuries in children was 24.7%, which was lower than other studies that reported a range of 35.8%-42.9% unintentional injuries among adolescents within the same time period, especially among the 13-15 age group [8][9][10][11][12]. Moreover, this study, being consistent with others, states that boys have a higher risk of injury and mortality [8][9][10][11]13,14].…”
Section: Introductionmentioning
confidence: 74%
“…A study done in Saudi Arabia showed that within the last 12 months, the prevalence of unintentional injuries in children was 24.7%, which was lower than other studies that reported a range of 35.8%-42.9% unintentional injuries among adolescents within the same time period, especially among the 13-15 age group [8][9][10][11][12]. Moreover, this study, being consistent with others, states that boys have a higher risk of injury and mortality [8][9][10][11]13,14]. Two studies in Saudi Arabia have reported a higher prevalence of unintentional injuries due to falls (62.9% and 31.9%, respectively), which is consistent with some studies that cite falls as being the most common cause of unintentional injury [7,[13][14][15].…”
Section: Introductionmentioning
confidence: 74%
“…Being male sex, bullied, physically attacked, or being in a physical fight were associated with unintentional injury. 20 Ssemugabho et al study among 1583 children from Ugandan slum community between 6 months of age and 18 years revealed 706 had suffered 787 unintentional injuries. 21 Mathur et al study among 6308 children up to 18 yrs belonging to slum areas of Ujjain findings indicate the annual incidence of all injuries was 16.6%, the incidence was significantly higher among boys compared to girls (20.2% versus 12.7%, respectively), was highest in age group 6-10 years of age (18.9%), and urban locations (17.5%).…”
Section: Discussionmentioning
confidence: 99%
“… 19 The most common type of injury among 3262 adolescents attending government school in Sri Lanka was cut or stab wounds (5.5%), followed by broken bones/dislocated joints (5.3%). 20 An Uganda 2018 study among 1583 children (between 6 months and 18 years old ) from Ugandan slums reported commonest injuries were cuts, bites, or open wounds (30.6%) and bruises or superficial injuries (28.6%) with the majority (75.5%) occurring at home. 21.…”
Section: Discussionmentioning
confidence: 99%
“…Surveys showed that unintentional injuries account for 3 of the 15 leading causes of death among children and adolescents under 20 years of age [ 4 ]. Traffic injury, drowning, burn and scalds, falls and poisoning accounted for 60% of the causes of death in children [ 6 ]. Worldwide, the second largest cause of disabled life expectancy (YLD) of children aged 10–24 years is unintentional injury, accounting for approximately 12.0%, approximately 6.0% in high-income countries and 16.0% in other underdeveloped areas in Sub-Sahara Africa [ 7 ].…”
Section: Introductionmentioning
confidence: 99%